Sweepers in the CNS: Microglial Migration and Phagocytosis in the Alzheimer Disease Pathogenesis. (14th May 2012) - Noda, Mariko; Suzumura, Akio
Abstract : Microglia are multifunctional immune cells in the central nervous system (CNS). In the neurodegenerative diseases such as Alzheimer's disease (AD), accumulation of glial cells, gliosis, occurs in the lesions. The role of accumulated microglia in the pathophysiology of AD is still controversial. When neuronal damage occurs, microglia exert diversified functions, including migration, phagocytosis, and production of various cytokines and chemokines. Among these, microglial phagocytosis of unwanted neuronal debris is critical to maintain the healthy neuronal networks. Microglia express many surface receptors implicated in phagocytosis. It has been suggested that the lack of microglial phagocytosis worsens pathology of AD and induces memory impairment. The present paper summarizes recent evidences on implication of microglial chemotaxis and phagocytosis in AD pathology and discusses the mechanisms related to chemotaxis toward injured neurons and phagocytosis of unnecessary debris.